Sustainable local development: consolidated framework for cross-sectoral cooperation via a systematic approach (2022)
Cross-sectoral cooperation (CSC) has gained recognition as the key to achieving sustainable development goals within a locality. However, existing studies focused on sustainable local development (SLD) initiatives resulting from CSC remain sparse. This article aims to review the CSC–SLD literature, using the Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) method. Research questions were constructed using the PICOC (population, intervention, comparison, outcomes, and context) structure. The identification of scientific works occurred through the search of relevant keywords, which resulted in a final set of 38 peer-reviewed manuscripts, from 1994 to 2021. First, the main driving forces for adopting CSC, to achieve SLD, which are dispersed at multiple levels, were captured and contextualised into the micro-, meso-, macro- and megaframework. Second, salient aspects addressed in the literature for effective CSC implementation were identified and classified into approaches, governance, structure, key actors, psychological and social aspects, and experiences themes. This resulted in a consolidated guiding principles framework for implementing CSC, to pursue SLD. Additionally, the use of theories in different aspects of CSC–SLD initiatives was discussed. This study informs the practitioners, policy-makers, and researchers the fundamentals that need to be considered when planning, designing, and implementing effective CSC interventions for SLD